1990
DOI: 10.1063/1.102912
|View full text |Cite
|
Sign up to set email alerts
|

Effect of energetic bombardment on the magnetic coercivity of sputtered Pt/Co thin-film multilayers

Abstract: Pt/Co multilayers are an attractive candidate for a magneto-optical recording medium. However, films sputter deposited in Ar have coercivities too small (100–350 Oe) to be practical in recording. By sputter depositing multilayers in Kr or Xe instead of Ar, we achieved coercivities ∼1000 Oe, suitable for recording. We attribute the lower coercivity of Ar-sputtered films to interfacial mixing of Pt and Co layers by energetic bombardment from Ar gas atoms that recoil from the Pt target.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
36
0

Year Published

1991
1991
2010
2010

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 108 publications
(37 citation statements)
references
References 9 publications
1
36
0
Order By: Relevance
“…Co/Pt multilayers with a total thickness of about 200 A were deposited either by electron-beam evaporation or by dc magnetron sputtering using Kr gas, on 2" glass disks with a pregrooved 2p lacquer and an 80 nm thick AIN optical enhancement layer. Recently, we reported that by using Kr instead of Ar, dense films were obtained with relatively high coercivities [6]. This is attributed to the sharper Co-Pt interfaces due to reduced bombardment by reflected sputter gas neutrals in case of sputtering with Kr gas.…”
Section: Introductionmentioning
confidence: 94%
“…Co/Pt multilayers with a total thickness of about 200 A were deposited either by electron-beam evaporation or by dc magnetron sputtering using Kr gas, on 2" glass disks with a pregrooved 2p lacquer and an 80 nm thick AIN optical enhancement layer. Recently, we reported that by using Kr instead of Ar, dense films were obtained with relatively high coercivities [6]. This is attributed to the sharper Co-Pt interfaces due to reduced bombardment by reflected sputter gas neutrals in case of sputtering with Kr gas.…”
Section: Introductionmentioning
confidence: 94%
“…Co/Pt multilayers, in particular, are ideally suited for this application, since bombardment with a suitable dose of energetic ions may induce interface mixing [3], thereby triggering a spin-reorientation transition from easy axis out-ofplane to easy axis in-plane [1]. He + irradiation at 30 keV ion energy and 10 16 ions/cm 2 dose was reported by Chappert et al [1] to effectively reduce the anisotropy, coercivity and Curie temperature in Pt/Co/Pt sandwich and multilayer structures.…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, various techniques [3][4][5][6] are well established for systematically tailoring the magnetic properties, however, limited mainly to ion-beam irradiation. For the latter, it is known that the coercivity of Co/ Pt multilayers falls with increasing ion dose, and this is assumed to be a result of collision-induced mixing of the different atoms, reducing the interfacial anisotropy.…”
mentioning
confidence: 99%